Analysis of Material Handling Safety in Construction Sites and Countermeasures for Effective Enhancement - C. N. Anil Kumar; M. Sakthivel; R. K. Elangovan; M. Arularasu (The Scientific World Journal)
One of many hazardous workplaces includes the construction sites as they involve several dangerous tasks. Many studies have revealed that material handling equipment is a major cause of accidents at these sites. Though safety measures are being followed and monitored continuously, accident rates are still high as either workers are unaware of hazards or the safety regulations are not being strictly followed. This paper analyses the safety management systems at construction sites through means of questionnaire surveys with employees, specifically referring to safety of material handling equipment. Based on results of the questionnaire surveys, two construction sites were selected for a safety education program targeting worker safety related to material handling equipment. Knowledge levels of the workers were gathered before and after the program and results obtained were subjected to a t-test analysis to mark significance level of the conducted safety education program.